Portaria SG/MPF nº 176, de 27 de fevereiro de 2015 - Lauro Pinto Cardoso Neto (DMPF-e, Brasília, DF, n. 39, 02 mar. 2015. Caderno Administrativo, p. 1., 2015)
Estabelece a estrutura organizacional da Secretaria Geral.